Kebijakan Pelaksanaan Pendidikan SD Islam Al Azhar 38 di Era Pandemi Covid-19 - Fitriana (La-Tahzan: Jurnal Pendidikan Islam, 2022)
Changes in the teaching and learning system that were initially implemented face-to-face at each institution were implemented at home. The learning from home policy requires creativity and learning innovation by teachers so that children are able to learn meaningfully at home. Learning in elementary schools which according to cognitive theory, children are still at a concrete operational stage requires a real learning process that is carried out at home in accordance with the context of the child in the surrounding environment. Policies in the learning process at SD Islam Al Azhar 38 Bantul were formulated jointly. SD Islam Al Azhar 38 Bantul during the Covid-19 pandemic by going through three stages, namely 1) pre Crisis, 2) Response to the Crisis, 3) post Crisis. This study uses a qualitative method with a type of case study. The research results showed that the pre-crisis stage was carried out by implementing the Covid-19 Prevention Literacy policy. The stages of response to the crisis are carried out by (a) online, (b) offline, and (c) Blanded learning. In the post-crisis stage, the principal conducts an evaluation and controls the various effects of the crisis to prevent future crises. Crisis management is prepared so that schools can be more responsive in dealing with crises in reducing their impact so that the learning process and activities can continue to run effectively.